A FRAMEWORK FOR EVALUATION OF MARINE SPATIAL DATA GEOPORTALS USING CASE STUDIES - Tavra, Marina; Cetl, Vlado; Duplančić Leder, Tea (GeoScience Engineering, 2014)
Need for a Marine Spatial Data Infrastructure (MSDI) as a component of a National Spatial Data Infrastructure (NSDI) is widely recognized. An MSDI is relevant not only for hydrographers and government planners, but also for many other sectors which takes interest in marine spatial data, whether they are data users, data providers, or data managers. An MSDI encompasses marine and coastal geographic and business information. For efficient use of Marine Spatial Data, it is necessary to ensure its valid and accessible distribution. A geoportal is a specialized web portal for sharing spatial information at different levels over the Internet. This paper re-examines the implementation of an MSDI and what it means for data custodians and end users. Several geoportals are reviewed (German and Australian) to determine their web services functionality, capabilities and the scope to which they support the sharing and reuse of Marine Spatial Data to assist the development of the Croatian MSDI Geoportal. This framework provides a context for better understanding the information bases on spatial data standards and a tool for evaluation of MSDI dissemination – Geoportal.